The type of diet consumed during prepuberty modulates plasma cholesterol, hepatic LXRα expression, and DNA methylation and hydroxymethylation during adulthood in male rats. - Ana Aguilar-Lozano; Berenice Palacios-González; Martha Guevara-Cruz; Armando R Tovar; Alam Palma-Guzman; Lilia G Noriega (PLoS ONE)
Childhood obesity increases the risk of developing metabolic diseases in adulthood, since environmental stimuli during critical windows of development can impact on adult metabolic health. Studies demonstrating the effect of prepubertal diet on adult metabolic disease risk are still limited. We hypothesized that a prepubertal control diet (CD) protects the adult metabolic phenotype from diet-induced obesity (DIO), while a high-fat diet (HFD) would predispose to adult metabolic alterations. Sprague-Dawley male rats were fed either a CD or a HFD during the prepubertal period (day 30-40 of age) and subsequently a chronic HFD or CD, respectively, until adulthood (day 220 of age). As controls, rats aged 30 days were exclusively fed a CD or a HFD until adulthood. Body weight and composition, metabolic rate, biochemical and hormonal plasma measurements, hepatic gene expression and methylation and hydroxymethylation levels were analyzed at ages 30, 40 and 220 days. The prepubertal CD prevented fat mass accumulation, lean mass loss and metabolic inflexibility, showed lower insulin, leptin and cholesterol concentrations in adulthood despite the chronic HFD. Notably, the prepubertal CD led to higher hepatic Lxrα expression, lower hepatic global DNA methylation and higher hydroxymethylation in adulthood despite a chronic HFD. Conversely, a prepubertal HFD decreased adult metabolic flexibility, increased serum cholesterol, and decreased Lxrα expression and global DNA hydroxymethylation, while also increasing DNA methylation levels despite a chronic CD. In summary, a prepubertal CD protected the adult metabolic phenotype from high cholesterol concentrations associated with increased hepatic Lxrα expression and lower hepatic global DNA methylation in adulthood, despite exposure to a chronic HFD. Conversely, a prepubertal HFD altered the adult metabolic phenotype.